A Trypanosoma cruzi zinc finger protein that is implicated in the control of epimastigote-specific gene expression and metacyclogenesis - Tavares, Thais S.; Lins Brandão Mügge, Fernanda; Grazielle-Silva, Viviane; Valente, Bruna M.; Goes, Wanessa M.; Oliveira, Antonio E. R.; Belew, Ashton T.; Guarneri, Alessandra A.; Pais, Fabiano S.; El-Sayed, Najib M.; Teixeira, Santuza M. R. (Parasitology, 2021)
Trypanosoma cruzi has three biochemically and morphologically distinct developmental stages that are programmed to rapidly respond to environmental changes the parasite faces during its life cycle. Unlike other eukaryotes, Trypanosomatid genomes contain protein coding genes that are transcribed into polycistronic pre-mRNAs and have their expression controlled by post-transcriptional mechanisms. Transcriptome analyses comparing three stages of the T. cruzi life cycle revealed changes in gene expression that reflect the parasite adaptation to distinct environments. Several genes encoding RNA binding proteins (RBPs), known to act as key post-transcriptional regulatory factors, were also differentially expressed. We characterized one T. cruzi RBP, named TcZH3H12, which contains a zinc finger domain and is up-regulated in epimastigotes compared to trypomastigotes and amastigotes. TcZC3H12 knockout (KO) epimastigotes showed decreased growth rates and increased capacity to differentiate into metacyclic trypomastigotes. Transcriptome analyses comparing wild type and TcZC3H12 KOs revealed a TcZC3H12-dependent expression of epimastigote-specific genes such as genes encoding amino acid transporters and proteins associated with differentiation (PADs). RNA immunoprecipitation assays showed that transcripts from the PAD family interact with TcZC3H12. Taken together, these findings suggest that TcZC3H12 positively regulates the expression of genes involved in epimastigote proliferation and also acts as a negative regulator of metacyclogenesis.